2014
DOI: 10.1155/2014/480201
|View full text |Cite
|
Sign up to set email alerts
|

Human Paraoxonase-1 Activity Is Related to the Number of CD4+ T-Cells and Is Restored by Antiretroviral Therapy in HIV-1-Infected Individuals

Abstract: Background. Paraoxonase-1 (PON1) activity is suggested to be altered in individuals infected with human immunodeficiency virus type-1 (HIV-1). We investigated PON1 activity in individuals receiving different regimens of highly active antiretroviral therapy (HAART). Methods. PON1 activity was evaluated in 91 HIV-1 seronegative and 624 HIV-1 infected individuals (115 were not undergoing therapy (ART-naïve), and 509 were receiving HAART). HIV-1 infected individuals were treated with the following: efavirenz (EFV;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…HIV-1 RNA levels and CD4 + T-cell numbers are indicators of the clinical stage of infection and are considered prognostic factors for the evaluation of the course of HIV-1 infection [16] [17]. The maintenance of CD4 + T-cell and CD8 + T-cell numbers characterizes the efficacy of HAART, which inhibits viral replication, slows the progression of immunodeficiency, and therefore restores immunity and increases the quality of life for HIV-1-infected individuals [18] [19]. Therefore, it is possible to infer a relationship between the number of CD4 + T-cells and serum hepcidin levels, which would be directly related to the best course of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 RNA levels and CD4 + T-cell numbers are indicators of the clinical stage of infection and are considered prognostic factors for the evaluation of the course of HIV-1 infection [16] [17]. The maintenance of CD4 + T-cell and CD8 + T-cell numbers characterizes the efficacy of HAART, which inhibits viral replication, slows the progression of immunodeficiency, and therefore restores immunity and increases the quality of life for HIV-1-infected individuals [18] [19]. Therefore, it is possible to infer a relationship between the number of CD4 + T-cells and serum hepcidin levels, which would be directly related to the best course of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis does not take into account the reduced levels of hepcidin, iron and ferritin observed in our ART-naïve group because those groups with different HAART regimens containing AZT did not display changes in the levels of these parameters, nor did these groups have any type of anemia or changes in iron metabolism. We can with some degree of certainty consider that modern HAART treatment can considerably overcome many of these effects [17] [19] [32].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that the PIs can promote reductions in the activity of PONs and an increased risk for atherosclerotic disease in HIV-1 patients has been shown through previous evidence. PON1 is an antioxidant enzyme present in serum is strongly associated with apolipoprotein-A1 (apoAl) from HDL and protects LDL against oxidative modifications [69,70]. The action of serum PON1 most likely occurs through the involvement of the enzyme in reverse cholesterol transport, a well-established anti-atherogenic propriety of HDL [71].…”
Section: Paraoxonasesmentioning
confidence: 99%
“…The inhibition of oxLDL by HDL is attributed to the high antioxidant content of the lipoprotein possibly due to the antioxidant properties of apoA1 and by the presence of other different antioxidant enzymes, such as glutathione peroxidase and PON, which prevent the formation of or degrade bioactive products of oxLDL [68]. Some studies have shown that the activity of PON1 may be affected and/or inactivated by oxidative stress, which could explain its reduced activity during HIV-1 infection [69][70][71]. In HIV-1 patients and those who undergo HAART, there is a significant increase in oxidative stress.…”
Section: Paraoxonasesmentioning
confidence: 99%
See 1 more Smart Citation